Storage and Management of XML Data Using Conventional Databases - Afonso de Sousa, Artur (2002)
As new standards for technology specifications related to XML are unveiled, and stable tools to implement them become available, the widespread usage of XML as an universal format for data exchange between heterogeneous systems (using the Internet) will increasingly become a reality. Therefore, in order to deal efficiently with the large amounts of XML data that will be generated in the near future it is imperative to find efficient alternatives for the storage and management of this special kind of data. In this paper we analyze, through examples, two possible approaches available for the storage and management of XML data, namely the object-relational and object-oriented databases.